Responses to Traumatic Brain Injury Screening Questions and Suicide Attempts among Those Seeking Veterans Health Administration Mental Health Services - Schneider, Alexandra L.; Hostetter, Trisha A.; Homaifar, Beeta Y.; Forster, Jeri E.; Olson-Madden, Jennifer H.; Matarazzo, Bridget B.; Huggins, Joe; Brenner, Lisa A. (Frontiers in Psychiatry, 2016)
Background: Psychometrically sound screening tools available to aid in the identification of lifetime history of traumatic brain injury (TBI) are limited. As such, the Traumatic Brain Injury-4 (TBI-4) was developed and implemented in a Veterans Health Administration (VHA) mental health clinic. To provide information regarding both the predictive validity and clinical utility of the TBI-4, the relationship between screening results and future suicide attempts was evaluated. Objective: The aim of this study was to determine whether a positive screen on the TBI-4 was associated with increased risk for suicide attempt within one year post screening. Methods: The TBI-4 was administered to 1,097 Veterans at the time of mental health intake. Follow-up data regarding suicide attempts for the year post-mental health intake were obtained from Suicide Behavior Reports (SBRs) in Veteran electronic medical records (EMRs). Fisher Exact tests were used to determine the proportion of suicide attempts by TBI-4 status. Results: In the year post TBI-4 screening, significantly more Veterans who screened positive had a documented suicide attempt as compared to those who screened negative (p=0.003). Conclusion: Those with a positive TBI screen at mental health intake had a higher proportion of SBRs than those who screened negative for TBI. Findings provided further psychometric support for the TBI-4. Moreover, results suggest the inclusion of this screen could prove to be helpful in identifying those who may be at risk for future suicide attempt within one year-post screening